The switch from oral contraception to hormonal replacement therapy in premenopausal women - Paszkowski, Tomasz; Wrona, Wojciech (Menopause Review/Przegląd Menopauzalny, 2006)
Hormonal changes that take place in the organism of a premenopausal women, especially with respect to her fertility potential, have been reviewed in detail by the authors of this paper. It is recommended to switch a premenopausal women from oral contraception (OC) to hormonal replacement therapy (HRT) – this paper presents the algorithms how to make such a switch and presents the multidirectional health benefits for the patients.